2015
DOI: 10.1016/j.csbj.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

News in livestock research — use of Omics -technologies to study the microbiota in the gastrointestinal tract of farm animals

Abstract: Technical progress in the field of next-generation sequencing, mass spectrometry and bioinformatics facilitates the study of highly complex biological samples such as taxonomic and functional characterization of microbial communities that virtually colonize all present ecological niches. Compared to the structural information obtained by metagenomic analyses, metaproteomic approaches provide, in addition, functional data about the investigated microbiota. In general, integration of the main Omics-technologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 90 publications
(174 reference statements)
4
78
0
6
Order By: Relevance
“…Mucosa samples showed higher species diversity than digesta in all GIT sections. Most of the studies characterizing chicken microbiota have focused on digesta of the different GIT sections (Deusch et al, 2015; Waite and Taylor, 2015). The mucosa or mucous layer, which is mainly composed by mucins and glycan, help the colonization of some groups of microorganisms in the gut (Donaldson et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Mucosa samples showed higher species diversity than digesta in all GIT sections. Most of the studies characterizing chicken microbiota have focused on digesta of the different GIT sections (Deusch et al, 2015; Waite and Taylor, 2015). The mucosa or mucous layer, which is mainly composed by mucins and glycan, help the colonization of some groups of microorganisms in the gut (Donaldson et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Las cuatro cepas molecularmente identificadas Lactobacillus brevis, Lactobacillus johnsonii, Enterococcus hirae y Pediococcus pentosaceus, clasificadas dentro del orden Lactobacillales, las que también son denominadas bacterias ácido lácticas. Las bacterias benéficas aisladas de la misma especie productiva, debido a su alta especificidad para su hospedero, resultado en una mejora de la salud general y un mejor crecimiento de los animales, en cerdo mejora su rendimiento productivo (Lamendella et al, 2011;Deusch et al, 2015). En el presente estudio (tabla 2) se obtuvieron mejores resultados de ICA con los tratamientos que contenían el inóculo bacteriano, posiblemente debido a que este grupo bacteriano tiene influencia positiva sobre la digestibilidad de los alimentos, lo que conlleva a mejorar la conversión alimenticia (Guerra et al, 2007).…”
Section: Resultados Y Discusiónunclassified
“…Sekelja et al also reported that a clear separation of microbial composition was seen between the upper gut (crop and gizzard), ileum and lower gut (cecum and colon) in broiler chickens (Sekelja et al 2012). That these distinctions may be due to different nutrient requirements, is a critical factor for colonizing the commensal bacteria because each section has different nutrient factors (Deusch et al 2015). The crop flora may be affected mainly by the microbial composition in the feed because the crop temporarily stores feed before digestion and is related to the breakdown of starch, whereas the ileal flora may be affected mainly by the nutrient composition of the ingested feed because ileum has a role involving the nutritional absorption of digested feed.…”
Section: Discussionmentioning
confidence: 99%